PENERAPAN METODE PEMBIASAAN DALAM MENINGKATKAN KEMANDIRIAN PADA ANAK KELOMPOK B1 DI TKIT YA BUNAYYA SAMBAS TAHUN PELAJARAN 2022-2023 - Meli Antika; Aslan; Elsa Mulya Karlina (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The aim of this research is to reveal the planning, implementation and evaluation of habituation methods in increasing independence in group B1 children at TKIT Ya Bunayya Sambas for the 2022-2023 academic year. This research uses a qualitative approach and is a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data display, and conclusions. The research results show that the planning for habituation methods to increase independence in group B1 children at TKIT Ya Bunayya Sambas for the 2022-2023 academic year consists of several steps, namely; 1) prepare a semester program; 2) prepare a weekly learning implementation plan; and 3) prepare a daily learning implementation plan. The implementation of the habituation method to increase independence in group B1 children at TKIT Ya Bunayya Sambas for the 2022-2023 academic year is carried out in three stages, namely initial activities, core activities and final activities. Meanwhile, the evaluation of habituation methods in increasing independence in group B1 children at TKIT Ya Bunayya Sambas for the 2022-2023 academic year was carried out in three stages, namely reflective evaluation, formative evaluation and summative evaluation.